Opposition-based moth swarm algorithm; Expert Systems with Applications; Vol. 184 - Oliva Navarro D. A. Diego Alberto; Esquivel-Torres S. Sara; Hinojosa S. Salvador; Perez-Cisneros M. Marco; Osuna-Enciso V. Valentin; Ortega-Sanchez N. Noe; Dhima G. Gaurav; Heidari A. A. Ali Asghar (2021, 2021)
Title screen